The Police in Nigeria: Meaning, Foundation, Scope and Essence - FOLAYAN, IJALANA (2018)
The paper examined the emergence and nature of the police with the various legal frameworks for the establishment and functions of the police in Nigeria with a view to assessing its meaning, foundation and scope as well as its essence and limits. These were with a view to undertaking holistic analysis and appraisal of the nature and extent of jurisdictional essence of policing Nigeria The study relied on primary and secondary sources of information. The primary source included unstructured interviews with relevant authorities, judicial decisions, statutory provisions establishing and providing functions for the Nigeria Police Force and rudimentary policing in Nigeria. The secondary source of information included books, journal articles, conference proceedings, newspaper publications and the internet. Information received was subjected to content analysis.The study found that the police is founded on a three-scope essence of (i) protection of life and property, (ii) maintenance of law and order and (iii) enhancing the administration of justice and that though enormous powers were conceded to the Nigeria Police for effective performance of its duties, police ineffectiveness mainly accounted for proliferation of law enforcement agencies in Nigeria. The study concluded and recommended that the issues of inadequate funding, lack of collaborative support and delineation of the various overlapping functions by other law enforcement agencies must be properly addressed if the Nigeria Police would be destined to fulfill its constitutional role to the best advantage of the people. Keywords: Foundation, The Police, Jurisdiction, Law Enforcement Agency, Scope of Functions